Exogenous prostaglandin D2 as a modulator in bovine endometritis: implications for reducing antibiotic use in dairy cattle - Yang, Xiaolin; Zhang, Shuangyi; Liu, Bo; Guo, Lili; Gong, Pengfei; Wu, Jingze; Zhao, Yi; Mao, Wei; Cao, Jinshan (Frontiers in Veterinary Science, 2025)
IntroductionBovine endometritis is a common postpartum uterine infection that significantly impacts the health and production performance of dairy cows, leading to economic losses for farms. Bovine endometritis is closely associated with pathogenic microorganisms, disturbances in uterine microecology, and localized inflammatory damage. Escherichia coli (E. coli) is the primary pathogenic bacterium responsible for bovine endometritis. Prostaglandin D2 (PGD2) is abundant in the uterine environment. However, its role in E. coli-induced endometritis remains largely unknown. We used bovine bone marrow-derived macrophages (BMDMs) and bovine endometrial tissue to investigate the specific genes and molecular mechanisms involved in E. coli-induced bovine endometritis.Methods and resultsTranscriptomic data show that E. coli infection significantly upregulated 2,141 genes and downregulated 2,381 genes in bovine BMDMs. E. coli activates various molecular functions in bovine BMDMs, with the most closely related being the inflammatory response, in which Prostaglandin-Endoperoxide Synthase 2 (PTGS2) plays a crucial role. Additionally, ELISA analysis revealed that E. coli infection significantly promoted the secretion of PGD2 in BMDMs. In the early stage of infection, ELISA results showed that exogenous PGD2 significantly promoted the secretion of TNF-α, IL-1β, and IL-6 in BMDMs and endometrial tissues, suggesting its role in enhancing the inflammatory response during early infection. Further q-PCR and immunofluorescence analyses demonstrated that PGD2 markedly upregulated the expression of damage-associated molecules, including high mobility group box 1 (HMGB-1) and hyaluronic acid-binding protein 2 (HABP-2). In addition, immunofluorescence and MTT assay results indicated that PGD2 enhanced the intracellular survival of E. coli in macrophages. H&E staining showed that PGD2 exacerbated pathological damage in bovine endometrial tissues. Contrastingly, at later stages, PGD2 suppresses the expression of inflammatory mediators, decreases E. coli survival, and alleviates tissue damage.DiscussionThese results not only deepen our understanding of the multifaceted role of exogenous PGD2 in uterine pathophysiology but also provide potential therapeutic implications for the treatment of bovine endometritis.